Characterization of Fusarium population associated with wilt of jojoba in Israel. (2nd February 2021) - Maymon, Marcel; Sharma, Gunjan; Hazanovsky, Marina; Erlich, Orly; Pessach, Shir; Freeman, Stanley; Tsror (Lahkim), Leah
Abstract: Fusarium wilt, caused by Fusarium oxysporum, is a major disease of jojoba, causing serious economic losses. This study was aimed at characterizing the Fusarium populations associated with jojoba in Israel. Fifty Fusarium isolates used in this study included 23 isolates from the 1990s ("past") and 27 recently isolated ("recent"). All the isolates were characterized by arbitrarily primed (ap)‐PCR and 16 representatives were additionally delineated using multilocus ( tef1, rpb1, rpb2 ) phylogeny and evaluated for their pathogenic potential. Consequently, 88% of the isolates were identified and characterized to the F . oxysporum species complex. The remaining 12% grouped within the F . fujikuroi, F . solani, and F . redolens species complexes. Variations in the infection rate (16.7%–100%), disease symptoms (0.08–1.25, on a scale of 0–3), and fungal colonization index (0.67–2.17, on a scale of 0–4) were observed within the tested isolates, with no significant differences between the past and recent isolates. The representative isolates were assigned to 11 groups based on ap‐PCR. Pathogenicity tests showed that isolates from Groups II, IV, and V were the most aggressive, whereas isolates from Groups III, VIII, and IX were the least aggressive. Among the tested isolates, F . oxysporum sensu lato was the most aggressive, followed by F . proliferatum, while F . nygamai was the least aggressive. This study demonstrates the complexity and genetic diversity of Fusarium wilt on jojoba in Israel, indicating possible multiple introductions of infected germplasm into the country. Abstract : This study characterized the Fusarium populations associated with jojoba wilt in Israel and Fusarium oxysporum sensu lato was determined as the most aggressive and predominant pathogen with high intraspecific genetic diversity.